SELF REGULATED LEARNING (STUDY FOR STUDENTS REGULAR AND TRAINING) - Hafiz Hidayat; Puji Gusri Handayani (Universitas Sultan Ageng Tirtayasa, 2018)
Self Regulated Learning (Study for regular and training students). This study aims to describe self regulated learning of regular students and training, and to test the difference of self regulated learning of regular and training class students.The samples used are 65 students of SMA N 5 Padang selected with purposive sampling and simple random sampling technique The instrument used is